PENGARUH PELATIHAN KEWIRAUSAHAAN DAN MOTIVASI KERJA TERHADAP MINAT BERWIRAUSAHA PENGHUNI LAPAS PEREMPUAN KELAS II A PONTIANAK - Maryani, Heni; Asriati, Nuraini; Achmadi, Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIncreased criminal activity that occurred in the community led to the populace of the Institutional Institution (LAPAS) will increase. Government as policy makers in this case hold coaching on the occupants of the prison so that the prisoners do not commit a crime again and have a working motivation. This research aims to analyze the influence of entrepreneurship training and work motivation on entrepreneurship interest in women in the second class A Pontianak. The method used in this research is Expos Fakto method with quantitative approach. The population in this research is all female prisoners who have attended 84 entrepreneurship training, the number of samples in this study is 51 people. Data collection techniques in this research are direct communication techniques, indirect communication techniques and documentary studies. The data collection tool used in this research is interview or quisioner or questionnaire and documentary study. The analysis of the research result using Multiple Linear Regression Analysis. The result of this study illustrates that there is significant influence of entrepreneurship training and motivation towards entrepreneurial interest of 92%. It means the better the entrepreneurial training and the work motivation organized by the women of the second class A Pontianak, then entrepreneurial interest will increase, and vice versa. Keywords: Entrepreneurship Training, Work Motivation, Entrepreneurial Interest